Implementasi Tata Kelola Aset Daerah Berbasis Akuntansi Pemerintahan: Evaluasi Kinerja dan Transparansi di Dinas Pemuda dan Olahraga Provinsi Maluku - Siti Arifah; Christina Sososutiksno; Dwi Hariyanti (Universitas Batanghari Jambi, 2026)
This study evaluates the implementation of SAP-based governmental accounting standards (Standar Akuntansi Pemerintahan/SAP) in asset governance at the Maluku Province Youth and Sports Office by integrating five pillars: SAP as the grammar of accountability, Public Asset Management/Value for Money (PAM/VfM) as the performance logic, good governance principles, Sistem Informasi Manajemen Daerah–Barang Milik Daerah (SIMDA-BMD) as the single source of truth, and the Committee of Sponsoring Organizations of the Treadway Commission (COSO) internal control framework. The results show that the basic elements of SAP have been implemented, but document non-uniformity, late cut-offs, and delayed register updates create recurring reconciliation gaps and reduce the Asset Data Quality Score (ADQS). Portfolio indicators utilization rate (UR), maintenance backlog ratio (MBR), condition index (CI), and lifecycle cost (LCC) are not yet active, so that accounting information does not flow into planning and budgeting. Gaps in the implementation of SIMDA-BMD strengthen ex post transparency, while weaknesses in risk assessment and monitoring reduce auditability.